THE PHYLOGENETIC STUDY OF NEW GUINEAN SPECIES OF ENDIANDRA (LAURACEAE) AND ITS RELATIONSHIPS WITH BEILSCHMIEDIA BASED ON MORPHOLOGICAL CHARACTERS - Deby Arifiani; Adi Basukriadi; Tatik Chikmawati (PTTI, 2012)
Endiandra species from New Guinea consist of species which vary in vegetative and reproductive characters. Staminal glands are present in 34 species out of 46 species of Endiandra in New Guinea, in constrast to the Bornean and Malay Peninsular species that lack of staminal glands. Beilschmiedia is a genus that often confused with Endiandra vegetatively, only flower characters can differentiate the two genera. This study was aimed to understand relationships of Endiandra species in New Guinea and to know the importance of staminal glands in grouping the New Guinean species of Endiandra. The relationships between Endiandra and Beilschmiedia based on the morphological characters will also be discussed. A phylogenetic analysis was performed to 47 morphological characters from 50 taxa, consisted of 41 species of Endiandra and 6 species of Beilschmiedia (as in-groups) with 3 species of Cryptocarya (as outgroups). Phylogenetic tree was constructed using Maximum Parsimony method. Phylogenetic tree showed that 47 in-groups taxa were grouped into five clades however with low bootstrap support. The species with and without glands are not separated from each other. Therefore, because of low bootstrap support, the monophyly of Endiandra and Beilschmiedia and the importance of staminal glands cannot be confirmed.